Preparation of acid-resistant sulfonated PVA/PAN pervaporation membranes for resource utilization of phosphogypsum leachate - Li Ma; Dongpu Hu; Wuqi Cai; Genyuan Zhang; Jing Wang; Yimeng Shi; Ziwen Dai; Sha Liang; Jiakuan Yang; Shushan Yuan (Desalination, 2026)

Vortex bionic structural composites fabricated by DLP 3D printing with high electromagnetic shielding effect and thermal conductive property - Jingxing Gui; Tao Zhang; Sha Long; Yingtao Li; Feiyue Zhou; Yuxuan Ma; Yuting Xue; Xueting Xu; Chunyan Hu; Baojiang Liu; Dan Yu; Wei Wang (Chemical Engineering Journal, 2026)

Glucose glycosylation enhances the functional properties of grass carp scale gelatin-derived TIPs via gut microbiota and metabolite regulation - Zi-Zi Hu; Ting-Ting Wu; Xin Li; Chun-Yan Peng; Su-Su Ye; Xiao-Mei Sha; Zong-Cai Tu (Food Research International, 2026)

Different types of activated carbon treatments for fish gelatin deodorization: insights into key flavor compounds and physicochemical properties changes - Li-Hong Wang; Xiao-Mei Sha; Wen-Hua Yang; Wen-Ming Xie; Zong-Cai Tu; Zi-Zi Hu (Food Chemistry, 2026)

Gastrointestinal digestive fate of squid cartilage collagen peptides: degradation characteristics and the key role of Gly-Pro skeleton structure - Xuanli Sha; Yueting Guo; Yan Fan; Tingting Yang; Liping Zheng; Shiqi Li; Hu Hou (Food Chemistry, 2026)

A ceRNA axis of lncRNA MSTRG.14394.1/miR-144-3p/NR1H3 responds to diverse bacterial PAMPs in teleost fish - Yishuai Li; Mengyang Chang; Suxu Tan; Wenwen Wang; Kunpeng Shi; Shaoqing Zang; Yiming Hu; Qingyang Fu; Songlin Chen; Zhenxia Sha (Fish & Shellfish Immunology, 2026)

Interfacial carbon-regulated charge transfer and ROS evolution in Ag3PO4 for enhanced photo-persulfate activation - Jiaxin Li; Chunmu Yu; Yu Zhou; Xiaojuan Chen; Yi Hu; Yuyu Chen; Nianmin Bo; Xinyu Ke; Jiahao Cui; Sha Xiao; Chunhui Cui; Ziyue Yang; et al. (Environmental Research, 2026)

Investigation of The Permeability Characteristics of Sediment-trapping Slow-release Ecological Dams and Their Filter Media - Hu Sha; Yi Ma; Yaofa Wang; Xiaogang Li; Juan Li (Water Resources Management, 2026)

Inflammatory response involved in cartilage degeneration induced by T-2 toxin: systematic review - Qian Li; Yikai Hu; Juan Zuo; Zaichao Dong; Tongtong Sha; Kangting Luo; Miao Wang; Huanxia Zhang; Yanjie Dou; Shuiyuan Yu; Fang-fang Yu (Mycotoxin Research, 2026)

Distance-decay relationship reveals both horizontal and vertical dispersal limitation and source–sink relationships of phytoplankton in a deep channel-type reservoir - Xiaofeng Tang; Jian Gao; Chengying Zhang; Junyi Wu; Yaxian Wang; Sha Xu; En Hu; Sisi Ye; Chao Chang; Ming Li (ENGINEERING Environment, 2026)

Substrate type and structural complexity drive macrobenthic diversity of coral reefs in the South China Sea - Peng-Jin Zhu; Li-Sha Hu; Zhan-Wei Zhao; Hong-Qiang Yang; Min Hui; Ze-Lin Chen; Yun-Wei Dong (Coral Reefs, 2026)

Plant growth patterns serve as a power switch governing microbial N use efficiency and N2O emission in an alpine meadow under climate change on the Qinghai-Tibet Plateau - Zheng Li; Yubao Sha; Huihui Liu; Guozheng Hu; Fen Zhao; Hasbagan Ganjurjav; Qingzhu Gao (Agriculture, Ecosystems & Environment, 2026)

A previously undescribed 3,4-secodammarane derivative from Ailanthus altissima - Yu-Sha Shi; Li-Lian Zhao; Li Huang; Su Hu; De-Feng Peng; Zhuo-Hong Li; Yun Deng; Da-Le Guo (Natural Product Research, 2026)

B-MARCO: a blockchain-driven multi-national auction and resource optimization framework for cross-border logistics and trade - Mei Sha; Shuang Li; Tao Zhang; Han Liu; Jianli Shen; Xiaohu Huang; Jiahua Hu (Frontiers in Marine Science, 2026)
Cross-border maritime logistics requires coordination among carriers, ports, customs authorities, and financial institutions, yet existing workflows are often constrained by fragmented regulatory data systems, inefficient dynamic capacity matching, and slow batch-based clearing. This paper proposes B-MARCO, a blockchain-driven multi-national auction and resource optimization framework for cross-border maritime logistics. B-MARCO integrates permissioned consortium coordination, rolling auction-based market clearing, a hybrid GA-GSA dispatching engine, and privacy-preserving access-control and compliance-verification components. The evaluation uses a semi-synthetic discrete-event simulation with a 7-day horizon, hourly decision intervals, 30 random seeds, and shared order streams across all configurations. Under a 5,000-orders/day workload, B-MARCO achieves a 91.80% transaction success rate and 21.53 h average end-to-end latency, compared with 60.09% and 36.66 h for the 24-hour batch-clearing baseline. Relative to a centralized rolling-matching baseline, it reduces average latency by 13.60%. The ablation results show that rolling auction clearing reduces latency, while smart-contract-based settlement-delay reduction is a major contributor to improved success and deadline performance. These findings support the value of combining rolling market clearing with spatial-temporal dispatch optimization in simulated cross-border maritime logistics, while the blockchain and cryptographic modules define the broader coordination, auditability, and data-governance architecture.

Spatial and temporal dynamics of the complexity, stability and community assembly of phytoplankton community in a deep channel-type reservoir - Xiaofeng Tang; Chengying Zhang; Sha Xu; En Hu; Chao Chang; Yuhan Ma; Daoping Xi; Ming Li (Journal of Environmental Sciences, 2026)

Functional antagonism and underlying regulatory pathways of haptoglobin splicing isoforms in the immune response of half-smooth tongue sole (Cynoglossus semilaevis) - Suxu Tan; Yixiao Hu; Wenwen Wang; Sen Han; Yu Bai; Yishuai Li; Kunpeng Shi; Shaoqing Zang; Yiming Hu; Zhenxia Sha (Fish & Shellfish Immunology, 2026)

Transformer-based fire detection using moderate resolution imaging spectroradiometer - Jin Sha; Xiuqing Hu; Bin Yang; Xu Huang; Shuang Li (Advances in Space Research, 2026)

Plastisphere denitrification dynamics shaped by soil acidification: Microbial Community and activity responses - Yu-Chen Li; Sha Zhao; Hu Li; Pei-Yuan Xu; Hong-Xia Cui; Jian-Qiang Su (Journal of Hazardous Materials, 2026)

Phage-based suppression of plasmid-mediated antibiotic resistance: A promising approach for antimicrobial stewardship - Yan-Zi Wang; Hu Li; Bei-Ning Xue; Xiao-Xu Zhao; Yu Rao; Sha Zhao; Kiandro J. Fortuna; Mao Ye; Jian-Qiang Su (Journal of Hazardous Materials, 2026)

Natural deep eutectic solvents (NADESs) as cryoprotectant for Lactiplantibacillus plantarum YR07: antifreeze mechanisms and applications - Sha sha Zheng; Li jun Tan; Qiong Pan; Yu fei Zhang; Wen di Zhang; Li fang Zou; Wei Cui; Yu Zhou; Ying ying Hu; Bao cai Xu (Food Research International, 2026)

miR-133a-3p promotes T-2 toxin-induced chondrocyte damage via targeting IGF1R - Kangting Luo; Lingyu Wang; Zhengyan Zhang; Yikai Hu; Chengyu Zhao; Shuiyuan Yu; Qian Li; Zaichao Dong; Tongtong Sha; Miao Wang; Juan Zuo; Yanjie Dou; et al. (Chemico-Biological Interactions, 2026)

Postharvest application of plasma-activated water to extend shelf life of strawberries - Yingman Gao; Yupan Zhu; Panfeng Guan; Leiyi Zhang; Xinyue Li; Guihuan Wei; Chenbin Hu; Ruichen Sha; Nanshan Du; Ruonan Ma; Zhen Jiao; Bing Li (Food Chemistry, 2026)

Self-adhesive conductive hydrogel electronic skin for self-powered electrical stimulation to enhance antibacterial activity and accelerate wound healing - Yuxiu Liu; Kun Wang; Rongchen Xu; Yaqi Wang; Changzhen Xu; Yanghui Chen; Bingqi Zhao; Jianan Niu; Wei Sha; Jiangwen Wang; Xue Bai; Hongbo Li; et al. (Chemical Engineering Journal, 2026)

Transcriptome–metabolome integration uncovers immune–metabolic defense mechanisms in Cynoglossus semilaevis against bacterial infections - Yishuai Li; Mengyang Chang; Suxu Tan; Mei Xin; Wenwen Wang; Kunpeng Shi; Shaoqing Zang; Yiming Hu; Zhenxia Sha (Aquaculture, 2026)

Advanced strategies for selective lithium extraction from spent lithium-ion battery cathodes - Ying Zheng; Ziwen Dai; Fan Yang; Zhaoyang Li; Guang Hu; Sha Liang; Wenbo Yu; Shushan Yuan; Huabo Duan; Liang Huang; Jingping Hu; Huijie Hou; et al. (Resources, Conservation and Recycling, 2026)

Engineered cytosolic and chloroplastic UDP-glucose epimerases distinctly modulate xylan interplay for size-tunable cellulose nanocrystals production in Oryza sativa - Yumeng Sun; Muzi Li; Meiyun Yang; Wennian Xia; Sha Wang; Zhongyi Wang; Yanting Wang; Liangcai Peng; Huizhen Hu; Ran Zhang (Carbohydrate Polymers, 2026)

Systematic druggable genome-wide Mendelian randomization identifies therapeutic targets for gout - Wei-quan Liao; Hui-ying Chen; Yu-ying Li; Li-juan Xiao; Zai-xing Qiu; Sha-sha Hu; Si-hui He; Lan Luo; Jing-jing Xie; Jian-yong Zhang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Covalent organic framework/PVA membranes for efficient phosphoric acid concentration via pervaporation - Wuqi Cai; Dongpu Hu; Huying Li; He Wen; Yimeng Shi; Jing Wang; Ziwen Dai; Wenbo Yu; Sha Liang; Jiakuan Yang; Shushan Yuan (Desalination, 2026)

Ti3C2-Cl-Bi12O17Cl2/Bi12O17Cl2 Mott-Schottky heterojunction with mixed noncovalent/covalent type to boost ultra-sensitive photoelectrochemical sensing of ciprofloxacin - Chu-Chu Hu; Qi-E Zhang; Shao-Peng Shi; Guo-Qing Zhao; Yan-Sha Gao; Ping Liu; Xun-Kuan Ye; Yan Pan; Hui-Qing Lv; Li-Min Lu (Chemical Engineering Journal, 2026)

Water-sediment regulation drives multi-taxon biodiversity and ecological network dynamics in the Yellow River Estuary - Cheng-Rui Yan; Li-Sha Hu; Xiao-Min Zhang; Shao-Wen Li; Fan Li; Yun-Wei Dong (Regional Studies in Marine Science, 2025)

Biogenic α-Mn2O3 excels in areas where commercial α-Mn2O3 performs poorly: Native and advanced oxidation degradation of atrazine - Huatao Sun; Huiyan Chen; Wuying Chen; Mingzhen Hu; Sha Chen; Yingjie Ma; Runjun Ou; Ding Li (Journal of Environmental Chemical Engineering, 2025)

Emission characteristics of full-volatility organic compounds from China's aluminum-products industry and their impacts on secondary organic aerosol and ozone potentials - Dongyang Wu; Qing'e Sha; Shan Jiang; Luyun Liu; Citao Zhang; Jialin Song; Junhao Xu; Haoqi Chen; Guanghui Li; Zhangmin Xiang; Bin Jiang; Zhuangmin Zhong; et al. (Environmental Research, 2025)

Thermal therapy of atherosclerotic plaques using ultrasonic phased-array system - Sha Yuan; Jiwen Hu; Chuangjian Xia; Qinlin Li; Chang Li (Medical & Biological Engineering & Computing, 2025)

Sustainable thermochromic coatings for pavement cooling and carbon offset under climate change - Yujing Chen; Aimin Sha; Wei Jiang; Wenxiu Jiao; Yangsen Cao; Xinzhou Li; Xiaotong Du; Kui Hu; Qun Lu (Transportation Research Part D: Transport and Environment, 2025)

Catalyzation of chlorine dioxide by manganese dioxide for efficient PAHs removal in industrial soil: New insight from relative reactive oxygen species generation - Xiaojun Hu; Qiying Li; Xuhan Lin; Bo Cheng; Zhiwen Cheng; Xuehong Yuan; Jinju Hou; Cheng Shen; Chenyan Sha; Fuwen Liu (Journal of Environmental Chemical Engineering, 2025)

Identifying gelatin source by mass spectrometry: A review - Xiao-Mei Sha; Le-Ying Yang; Hui Wang; Jie Cheng; Hao-Sheng Luo; Li-Jun Zhang; Zi-Zi Hu; Zong-Cai Tu (Food Chemistry, 2025)

The effect of uracil on the freeze-drying survival rate of Lactiplantibacillus plantarum YR07 based on transcriptome analysis - Sha-sha Zheng; Wen-di Zhang; Li-jun Tan; Li-fang Zou; Ying-ying Hu; Liu Yang; Bao-cai Xu (Food Microbiology, 2025)

Recessive variants in TWNK cause syndromic and non-syndromic post-synaptic auditory neuropathy through MtDNA replication defects - Xue Gao; Ying Ma; Wei-Qian Wang; Guo-Jian Wang; Kun Yang; Jin-Cao Xu; Sha-Sha Huang; Xiang Wang; Li-Min Hu; Xi Wang; Qiu-Quan Wang; Zhen-Dong Wang; et al. (Human Genetics, 2025)

Closed-loop recycling of lead iodide precursor from waste organic solvents in the production of perovskite solar cells: Toward sustainable photovoltaics - Qingfang Zou; Zifan Lin; Zhaoyang Li; Guang Hu; Shifa Zhou; Ying Zheng; Liang Huang; Sha Liang; Huabo Duan; Shushan Yuan; Chao Chen; Ling Xu; et al. (Waste Management, 2025)

Insights into solidification mechanism of Cr(III) and Cr(VI) in chromite ore processing residue via composite geopolymers synthesized from calcined red mud and granulated blast furnace slag - Yan Ke; Sha Liang; Huabo Duan; Junda Quan; Xingwu Li; Huijie Hou; Jingping Hu; Yin Yang; Xing Liu; Yibing Zuo; Jiakuan Yang (Journal of Hazardous Materials, 2025)

DCNet: Full waveform inversion with difference convolution - Li-Sha Fu; Chang-Yang Hu; Leting Tan; Huawei Liao; Qiang Zhang; Fan Min (Journal of Applied Geophysics, 2025)

Charge/conformation-transformable phosphopeptide@hollow covalent organic frameworks as molecular gates for electrochemical analysis - Lin Wang; Minghui Wang; Gaoxiang Wang; Haojie Xie; Yu Hang; Dongmei Zhang; Sha Zhu; Xiafei Hu; Genxi Li (Chemical Engineering Journal, 2025)

Sustainable remediation of butyl xanthate-contaminated mine wastewater by combining emergent macrophyte Cyperus alternifolius with a versatile bacterial isolate - Qi Liu; Yao-Yao Ye; Sha Yang; Cheng-Yu Cui; Huan Du; Jin-Cheng Ye; Ji-Liang Cheng; Rui-Wen Hu; Lei Xiang; Bai-Lin Liu; Yan-Wen Li; Quan-Ying Cai; et al. (Journal of Hazardous Materials, 2025)

A novel bioreactor developed for the intensification of high-viscosity aerobic fermentation processes - Qian Chen; Kai Hu; Quanfei Li; Kai Yang; Chao Zhang; Weiwei Huang; Yibin Qiu; Yian Gu; Liang Sun; Peng Lei; Jian Xue; Sha Li; et al. (Chemical Engineering Journal, 2025)

A closed-loop ammonium acetate leaching-electrodeposition route for metallic lead recovery from spent lead paste - Jiangbei Liang; Sha Liang; Mingyang Li; Zhaoyang Li; Guang Hu; Huabo Duan; Jiakuan Yang; R.Vasant Kumar (Resources, Conservation and Recycling, 2025)

Experimental evidence for viral impact on microbial community, nitrification, and denitrification in an agriculture soil - Hu Li; Sha Zhao; Meng-Ke Gao; Yanyan Zhou; Bo Xu; Le-Yang Yang; Xiao-Ru Yang; Jian-Qiang Su (Journal of Hazardous Materials, 2025)

Bismuth-selenium nanocomposite clusters inhibit tobacco bacterial wilt by disrupting bacterial morphology and promoting vegetative oxidative phosphorylation - Yanyu Hu; EnDong Yang; Yanping Qiu; Bangjia Yang; Shenghui Gao; Sha Li; Yuanyuan Cao; Dongdong Sun (Journal of Cleaner Production, 2025)

Effect of extraction temperature on the detection in characteristic peptides of gelatin from grass fish scale and its identification in different food systems - Zi-Zi Hu; Wen-Li Jiang; Xiao-Mei Sha; Zong-Cai Tu (Food Chemistry, 2025)

Land use types, basin characteristics and water quality together shape riverine phytoplankton community composition and diversity - Sisi Ye; Sha Xu; Mi Ren; Chao Chang; En Hu; Ming Li (Journal of Environmental Management, 2025)

A novel framework for river organic carbon retrieval through satellite data and machine learning - Shang Tian; Anmeng Sha; Yingzhong Luo; Yutian Ke; Robert Spencer; Xie Hu; Munan Ning; Yi Zhao; Rui Deng; Yang Gao; Yong Liu; Dongfeng Li (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Biomonitoring and food surveillance on heavy metals reveal need for food safety in a coastal region - Xin Zhang; Xiaoqian Yang; Xiaoyue Hu; Zhonghua Meng; Zhigang Yu; Zhan Sun; Ying Zhang; Zhifeng Yang; Sha Li; Jia-Sheng Wang; Qiang Jia; Lanzheng Liu; et al. (Food Research International, 2025)

Critical evaluation of extracellular polymeric substances extraction methods: Extraction efficiency, molecular characteristics, and heavy metals binding properties - Bei Ou; Xueyang Hu; Wenbo Yu; Fanhao Meng; Wen Li; Sha Liang; Shushan Yuan; Huabo Duan; Huijie Hou; Keke Xiao (Science of The Total Environment, 2025)

A Protocol for Body MRI/CT and Extraction of Imaging-Derived Phenotypes (IDPs) from the China Phenobank Project - Chengyan Wang; Shuo Wang; Sha Hua; Ruokun Li; Yan Li; Zhang Shi; Kai Feng; Lizhen Lan; Meng Liu; Xutong Kuang; Xueqin Xia; Shihai Zhao; et al. (Phenomics, 2024)

Reseeding increased plant biomass production and soil fertility, but not plant species diversity in degraded grasslands in China - Hasbagan Ganjurjav; Mingjie Li; Ling Han; Yubao Sha; Zheng Li; Xuyang Han; Guoxu Ji; Rihan Wu; Yandan Ma; Guozheng Hu; Elise Gornish; Qingzhu Gao (Journal of Environmental Management, 2024)

Genomics‐Informed Range Predictions Under Global Warming Reveal Reduced Adaptive Diversity Whilst Buffering Range Shifts for a Marine Snail - Xiao‐Nie Lin; Chao‐Yi Ma; Li‐Sha Hu; Ming‐Ling Liao; Lin‐Xuan Ma; Peter R. Teske; Ary Hoffmann; Yun‐Wei Dong (Global Change Biology, 2024)
Understanding the genetic basis of local adaptation in thermal performance is useful for predicting species distribution shifts under anthropogenic climate change. Many species are distributed across multiple biogeographic regions, and the uniquely adapted populations in each region may respond to future ocean warming with distinct distribution changes. In the present study, we investigated phylogeographic patterns, thermal sensitivity, and genetic differentiation in the intertidal snail Littorina brevicula along China's coast. Whole‐genome sequencing results based on a newly assembled chromosome‐level genome revealed two genetic lineages, with a north–south divergence that is linked to the thermal environment. Within each lineage, individuals could be further subdivided into genetic subgroups that differ at key genomic loci underpinning differences in upper heat tolerance. Heat stress drives adaptive divergence across multiple levels of organization, from the individual to the biogeographic level. Taking into account genetic diversity associated with variation in heat tolerance, a physiological species distribution model (pSDM) was applied to predict the distributions of the different genetic subgroups in response to climate change. Both northern and southern lineages were predicted to experience declines in habitat suitability under a 4°C future warming scenario, and that a genotypic subset of snails from the southern lineage may even be driven to extinction. These findings illustrate that even when a species' range is maintained, it can nonetheless experience a significant decrease in adaptive diversity as a result of climate change. The integrated approach presented here, which considered both physiological and adaptive genetic variation at the level of individuals within a biogeographical context, provided new insights into how marine species can respond to global warming.

The superior adsorption capacity of biogenic α-Mn2O3 in comparison to chemogenic α-Mn2O3 for five divalent heavy metal cations and the adsorption mechanism of biogenic α-Mn2O3: Experimental and DFT investigations - Mingzhen Hu; Huatao Sun; Jun Luo; Sha Chen; Ding Li (Journal of Environmental Chemical Engineering, 2024)

Levels, sources, and health risk assessment of phthalate acid esters in indoor dust of various microenvironments in university - Jun Pan; Xin Li; Ping Ding; Haojie Luo; Sha Cai; Qing Ge; Liuyi Zhang; Guocheng Hu (Chemosphere, 2024)

Multi-omics insights into the function and evolution of sodium benzoate biodegradation pathway in Benzoatithermus flavus gen. nov., sp. nov. from hot spring - Chao-Jian Hu; Yi-Qing Lv; Wen-Dong Xian; Jian-Yu Jiao; Zheng-Han Lian; Sha Tan; Meng-Meng Li; Zhen-Hao Luo; Ze-Tao Liu; Ai-Ping Lv; Lan Liu; Mukhtiar Ali; et al. (Journal of Hazardous Materials, 2024)

Alleviation of cadmium uptake in rice (Oryza sativa L.) by iron plaque on the root surface generated by Providencia manganoxydans via Fe(II) oxidation - Ding Li; Zeping He; Sha Chen; Jinyuan Chen; Zhexu Ding; Jun Luo; Zongpei Li; Yuanyi Hu (Archives of Microbiology, 2024)

Innovative insights into dry fermented sausages flavor: Unraveling the impact of varied lactobacillus genera-driven fermentation - Sha-sha Zheng; Ying-ying Hu; Li-jun Tan; Liu Yang; Chun-yu Wang; Bao-cai Xu (Food Bioscience, 2024)

Parametric resonance of pipe conveying pulsating fluid with initial geometric imperfection - Meng-Yuan Hao; Hu Ding; Xiao-Ye Mao; Sha Wei; Li-Qun Chen (Ocean Engineering, 2024)

Applications of 3D modeling in cryptic species classification of molluscs - Cheng-Rui Yan; Li-Sha Hu; Yun-Wei Dong (Marine Biology, 2024)

Enhancing phosphorus removal by novel porous concrete fabricated with alkali-activated aggregate derived from industrial solid wastes - Junda Quan; Xilong Li; Sha Liang; Guang Hu; Xingwu Li; Wenbo Yu; Shushan Yuan; Huabo Duan; Jingping Hu; Huijie Hou; Xiong Shi; Jiakuan Yang (Resources, Conservation and Recycling, 2024)

Water-sediment regulation affects community structures of macrobenthic mollusks in the Yellow River estuary and adjacent waters - Li-Sha Hu; Xiao-Min Zhang; Shao-Wen Li; Fan Li; Yun-Wei Dong (Regional Studies in Marine Science, 2024)

Contrasted changes of sea-surface salinity in the southern and northern Okinawa Trough since the mid-Holocene - Dongling Li; Yanjuan Wu; Marit-Solveig Seidenkrantz; Anne de Vernal; Bangqi Hu; Bing Song; Hui Jiang; Longbin Sha (Global and Planetary Change, 2024)

Detection and analysis of landslide geomorphology based on UAV vertical photogrammetry - Rui Bi; Shu Gan; Xiping Yuan; Kun Li; Raobo Li; Weidong Luo; Cheng Chen; Sha Gao; Lin Hu; Zhifu Zhu (Journal of Mountain Science, 2024)

Genome-wide identification and quantification of salinity-responsive Na+/K+-ATPase α-subunits in three salmonids - Yue Su; Shuang-En Yu; Yong-Xu Sun; Liang Zhang; Yue Tan; Yu-Yang Zhang; Shuo Wang; Yan-Gen Zhou; Li-Sha Hu; Yun-Wei Dong (Aquaculture, 2024)

Revolutionizing soil heavy metal remediation: Cutting-edge innovations in plant disposal technology - Yucheng Hu; Junbang Wang; Yongsheng Yang; Sha Li; Qinghua Wu; Eugenie Nepovimova; Xiujuan Zhang; Kamil Kuca (Science of The Total Environment, 2024)

Peroxymonosulfate activation by trace iron(III) porphyrin for facile degradation of organic pollutants via nonradical oxidation - Lu Liu; Jingping Hu; Jianjian Tang; Sijing Chen; Longsheng Wu; Zhen Li; Huijie Hou; Sha Liang; Jiakuan Yang (Chemosphere, 2024)

Enhanced O/W emulsion stability and betanin protection using yeast protein and chitooligosaccharide: Comparative insights from complex coacervation and layer-by-layer methods - Jiangnan Hu; Rui Yang; Runxuan Chen; Chang Liu; Xinmei Sha; Ku Li; Hui Guo; Yuyu Zhang (Food Hydrocolloids, 2024)

Stay in touch with the endoplasmic reticulum - Sha Sun; Gan Zhao; Mingkang Jia; Qing Jiang; Shulin Li; Haibin Wang; Wenjing Li; Yunyun Wang; Xin Bian; Yan G. Zhao; Xun Huang; Ge Yang; et al. (Science China Life Sciences, 2024)

Characterization of a novel algicidal bacteria Arenibacter sp. strain 6A1 and its application to eliminate harmful algal blooms - Sha Wu; Jing Tong; Jiahuan Chen; Minchun Chen; Liyan Wang; Shuangfei Li; Zhangli Hu; Huirong Chen (Frontiers in Marine Science, 2024)
Hazardous impacts caused by harmful algal blooms (HABs) have facilitated the development of novel effective approaches for controlling the frequent HABs. Recently, bacteria with algicidal effects, as a promising alternative tool for eliminating the HABs-forming species have received wide concerns. In the present study, a marine bacterial strain 6A1 with potent algicidal activity was successfully isolated from a bloom of Akashiwo sanguinea , and the characteristics related to its algicidal action were systematically investigated. Sequencing results of 16S rDNA suggested that this bacterium belongs to the genus Arenibacter in the family Flavobacteriaceae, while the phylogenetic analysis revealed that Arenibacter sp. strain 6A1 was the only algicidal bacterium in Arenibacter to date, according to the best of our knowledge. Arenibacter sp. strain 6A1 had an extraordinarily high algicidal performance when it was added to A. sanguinea culture with a volume fraction of 1.5% for 2 h. The algicidal performance of strain 6A1 was concentration-dependent and time-dependent. The best algicidal efficacy of strain 6A1 was seen during the stationary phase, while the resistance of A. sanguinea to strain 6A1 declined as the growth cycle progressed. Subsequently, the indirect algicidal mode of Arenibacter sp. strain 6A1 was verified and the algicidal compounds produced by strain 6A1 were proved to be heat-resistant. Further research showed that strain 6A1 caused a severe damage in photosynthesis, oxidative stress, and also damage in three HABs-forming algae to varying degrees. The greatest algicidal performance was found on unarmored dinoflagellate A. sanguinea , followed by raphidophyte Chattonella antiqua and armored dinoflagellate Alexandrium tamarense . The Arenibacter sp. strain 6A1 exhibited selective algicidal activity on a wide range of algal species, primarily targeting Pyrrophyta and Ochrophyta. The proposed bacteria (strain 6A1) can be a powerful and eco-friendly tool for emergency treatment of HABs caused by certain algal species in coastal water bodies.

Efficient piezo-photocatalysis of Bi2O2(OH)NO3/BiOI heterojunction: Collaboration of piezoelectric polarization and interface electric field - Yuanrui Li; Xiaolei Zhang; Rui Sha; Tong Li; Cheng Hu; Shuchen Tu; Fang Chen; Hongwei Huang (Chemical Engineering Journal, 2024)

Climate-shaped vegetation dominated the spatial pattern of the Bowen ratio over terrestrial ecosystems in China - Mingyu Sun; Guirui Yu; Zhi Chen; Tianxiang Hao; Meng Yang; Xianjin Zhu; Weikang Zhang; Lang Han; Zhaogang Liu; Lexin Ma; Xiaojun Dou; Yuan Yao; et al. (Agricultural and Forest Meteorology, 2024)

In vitro gastrointestinal digestion of thermally reversible and irreversible fish gelatin induced by microbial transglutaminase - Xiao-Mei Sha; Ting Fang; Jia-Hui Zhang; Sheng Shu; Wen-Li Jiang; Zi-Zi Hu; Zong-Cai Tu (Food Hydrocolloids, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Environmentally sound management of industrial solid waste: A paradigm of proposed bi-tetrahedron - Yan Ke; Ye Chen; Sha Liang; Jingping Hu; Huijie Hou; Junda Quan; Xingwu Li; Huabo Duan; Shushan Yuan; Jiakuan Yang (Resources, Conservation and Recycling, 2023)

Phase change materials in food: Phase change temperature, environmental friendliness, and systematization - Chi Hu; Lishan Sha; Chongxing Huang; Wanru Luo; Bo Li; Haohe Huang; Chenglong Xu; Kaikai Zhang (Trends in Food Science & Technology, 2023)

Surviving hot summer: Roles of phenotypic plasticity of intertidal mobile species considering microhabitat environmental heterogeneity - Yong-Xu Sun; Li-Sha Hu; Yun-Wei Dong (Journal of Thermal Biology, 2023)

Effects of phenolic acid analogs on the structure, iron oxidation/iron release, and stability of phytoferritin - Jiangnan Hu; Lina Shi; Lei Zhu; Xinmei Sha; Yue Li; Junrui Ma; Qing Zhang; Rui Yang (Food Bioscience, 2023)

Dual network hydrogel coatings based on recombinant mussel protein with enhanced antibacterial and super-lubrication properties for urinary catheter applications - Yubo Hu; Youzhi Qiao; Peng Lei; Yian Gu; Liang Sun; Yibin Qiu; Sha Li; Hong Xu; Rui Wang (Chemical Engineering Journal, 2023)

Revealing the roles of chemical communication in restoring the formation and electroactivity of electrogenic biofilm under electrical signaling disruption - Qian Zhu; Dingkang Qian; Mengjiao Yuan; Zhen Li; Ziming Xu; Sha Liang; Wenbo Yu; Shushan Yuan; Jiakuan Yang; Huijie Hou; Jingping Hu (Water Research, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

AtSAMS regulates floral organ development by DNA methylation and ethylene signaling pathway - Wenli Hu; Shuang Hu; Shaozhuang Li; Qi Zhou; Zijing Xie; Xiaohua Hao; Sha Wu; Lianfu Tian; Dongping Li (Plant Science, 2023)

Corrigendum to “Generation of high-valent iron-oxo porphyrin cation radicals on hemin loaded carbon nanotubes for efficient degradation of sulfathiazole” [J. Hazard. Mater. 444 (2023) 130402] - Sijing Chen; Zhen Li; Longsheng Wu; Lu Liu; Jingping Hu; Huijie Hou; Sha Liang; Jiakuan Yang (Journal of Hazardous Materials, 2023)

Cation-deficient T-Nb2O5/graphene Hybrids synthesized via chemical oxidative etching of MXene for advanced lithium-ion capacitors - Lei Wang; Xiong Zhang; Chen Li; Yanan Xu; Yabin An; Wenjie Liu; Tao Hu; Sha Yi; Kai Wang; Xianzhong Sun; Yue Gong; Zhong-Shuai Wu; et al. (Chemical Engineering Journal, 2023)

Novel PbO@C composite material directly derived from spent lead-acid batteries by one-step spray pyrolysis process - Wenhao Yu; Mingyang Li; Sha Liang; Qi Xu; Peiyuan Zhang; Huijie Hou; Jingping Hu; Jiakuan Yang (Waste Management, 2023)

A temporospatial assessment of environmental quality in urbanizing Ethiopia - Jian Sun; Yang Hu; Yang Li; Lingfei Weng; Haonan Bai; Feidan Meng; Tao Wang; Huanzheng Du; Dong Xu; Sha Lu (Journal of Environmental Management, 2023)

Mobile Phone Imaging Point Cloud Modelling for 3D Recording and Measurement of Small Scenes of Suspected Fossil Outcrops Found in the Field - Gao Sha; Gan Shu; Yuan Xiping; Hu Lin; Bi Rui; Li Raobo; Yang Ming (Geoheritage, 2023)

Contribution of the TGFβ signaling pathway to pigmentation in sea cucumber (Apostichopus japonicus) - Linlin Yao; Bin Zhao; Qi Wang; Xuyang Jiang; Sha Han; Wei Hu; Chenglin Li (Frontiers in Marine Science, 2023)
Pigmentation mediated by the transforming growth factor β (TGFβ) signaling pathway is a key trait for understanding environmental adaptability and species stability. In this study, TGFβ signaling pathway members and their expression patterns in different color morphs of the sea cucumber Apostichopus japonicus were evaluated. Using a bioinformatics approach, 22 protein sequences of TGFβ signaling pathway members in A. japonicus were classified, including 14 that were identified for the first time in the species, including 7 ligands, 6 receptors, and 1 R-Smad. We further evaluated mRNA expression data for different color morphs and pigmentation periods. These results support the hypothesis that both subfamilies of the TGFβ superfamily, i.e., the TGFβ/activin/Nodal and BMP/GDF/AMH subfamilies, are involved in the regulation of pigmentation in A. japonicus . The former subfamily was complete and contributes to the different color morphs. The BMP/GDF/AMH subfamily was incomplete. BMP2/4-induced differentiation of white adipocytes was regulated by the BMP2/4–ACVR2A–Smad1 signaling pathway. These findings provide insight into the TGFβ family in early chordate evolution as well as the molecular basis of color variation in an economically valuable species.

Generation of high-valent iron-oxo porphyrin cation radicals on hemin loaded carbon nanotubes for efficient degradation of sulfathiazole - Sijing Chen; Zhen Li; Longsheng Wu; Lu Liu; Jingping Hu; Huijie Hou; Sha Liang; Jiakuan Yang (Journal of Hazardous Materials, 2023)

Effect of phenol formaldehyde-associated microplastics on soil microbial community, assembly, and functioning - Hu Li; Qiu-Ping Luo; Sha Zhao; Yan-Yan Zhou; Fu-Yi Huang; Xiao-Ru Yang; Jian-Qiang Su (Journal of Hazardous Materials, 2023)

The detection of major clades and new species of Mallocybe (Inocybaceae, Agaricales) from China with elongate cheilocystidia - Jian-Hua Hu; Wen-Jie Yu; Lun-Sha Deng; Yu-Guang Fan; Tolgor Bau; Li-Ping Tang; Wen-Fei Lin; Chun-Ying Deng (Mycological Progress, 2023)

Impacts of maize hybrids with different nitrogen use efficiency on root‐associated microbiota based on distinct rhizosphere soil metabolites - Keke Li; La Chen; Wenjun Shi; Conghui Hu; Ye Sha; Guozhong Feng; Entao Wang; Wenxin Chen; Xinhua Sui; Guohua Mi (Environmental Microbiology, 2023)
Plant genotypes shape root‐associated microbiota that affect plant nutrient acquisition and productivity. It is unclear how maize hybrids modify root‐associated microbiota and their functions and relationship with nitrogen use efficiency (NUE) by regulating rhizosphere soil metabolites. Here, two N‐efficient (NE) (ZD958, DMY3) and two N‐inefficient (NIE) maize hybrids (YD9953, LY99) were used to investigate this issue under low N (60 kg N ha −1 , LN) and high N (180 kg N ha −1 , HN) field conditions. NE hybrids had higher yield than NIE hybrids under LN but not HN. NE and NIE hybrids recruited only distinct root‐associated bacterial microbiota in LN. The bacterial network stability was stronger in NE than NIE hybrids. Compared with NIE hybrids, NE hybrids recruited more bacterial taxa that have been described as plant growth‐promoting rhizobacteria (PGPR), and less related to denitrification and N competition; this resulted in low N 2 O emission and high rhizosphere NO 3 − ‐N accumulation. NE and NIE hybrids had distinct rhizosphere soil metabolite patterns, and their specific metabolites were closely related to microbiota and specific genera under LN. Our findings reveal the relationships among plant NUE, rhizosphere soil metabolites, root‐associated microbiota, and soil nutrient cycling, and this information is informative for breeding NE crops.

Iron-calcium reinforced solidification of arsenic alkali residue in geopolymer composite: Wide pH stabilization and its mechanism - Yingfei Sun; Pan Zhang; Zhen Li; Jing Chen; Yan Ke; Jingping Hu; Bingchuan Liu; Jiakuan Yang; Sha Liang; Xintai Su; Huijie Hou (Chemosphere, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

Traceability and identification of fish gelatin from seven cyprinid fishes by high performance liquid chromatography and high-resolution mass spectrometry - Xiao-Mei Sha; Wen-Li Jiang; Zi-Zi Hu; Li-Jun Zhang; Zuo-Hua Xie; Ling Lu; Tao Yuan; Zong-Cai Tu (Food Chemistry, 2023)

Evolving a high-performance bio-imaging tool derived from a compact fluorophore as well as creating a reaction-based fluorescent probe for precise determination of Ag+ - Zi Yi Xu; Xiao Hu Wang; Sha Li Huang; Jing Rong Chen; Hong Qun Luo; Nian Bing Li (Chemical Engineering Journal, 2023)

Substitution of soybean meal with Clostridium autoethanogenum protein in grass carp (Ctenopharygodon idella) diets: Effects on growth performance, feed utilization, muscle nutritional value and sensory characteristics - Rongrong Xue; Handong Li; Sha Liu; Zechao Hu; Qin Wu; Hong Ji (Animal Feed Science and Technology, 2023)

Phylogenetic analyses, morphological studies, and muscarine detection reveal two new toxic Pseudosperma (Inocybaceae, Agaricales) species from tropical China - Li-Na Zhao; Wen-Jie Yu; Lun-Sha Deng; Jian-Hua Hu; Yu-Peng Ge; Nian-Kai Zeng; Yu-Guang Fan (Mycological Progress, 2022)

ML323, a USP1 inhibitor triggers cell cycle arrest, apoptosis and autophagy in esophageal squamous cell carcinoma cells - Yaxin Sun; Beibei Sha; Wenjing Huang; Miaomiao Li; Shan Zhao; Yuan Zhang; Jie Yan; Zheng Li; Jingwen Tang; Peiyan Duan; Jianxiang Shi; Pei Li; et al. (Apoptosis, 2022)

Armochaetoglasins J and K: new cytochalasans from Chaetomium globosum - Li Cheng; Xi Zheng; Qin Li; Meng-Sha Wei; Chun-Mei Chen; Hu-Cheng Zhu; Chang-Li Zeng; Xin-Cai Hao; Yong-Hui Zhang (Natural Product Research, 2022)

Analysis of geomorphologic features of the circular structure in the south of Lufeng Dinosaur Valley - Hu Lin; Gan Shu; Yuan Xiping; Yang MingLong; Gao Sha; Bi Rui; Li Yan (Earth Science Informatics, 2022)

Hydrogen Sulfide Maintains Good Nutrition and Delays Postharvest Senescence in Postharvest Tomato Fruits by Regulating Antioxidative Metabolism - Ting-Ying Zhong; Gai-Fang Yao; Sha-Sha Wang; Ting-Ting Li; Ke-Ke Sun; Jun Tang; Zhong-Qin Huang; Feng Yang; Yan-Hong Li; Xiao-Yan Chen; Lan-Ying Hu; Hua Zhang; et al. (Journal of Plant Growth Regulation, 2021)

Carbonic Anhydrase III Attenuates Hypoxia-Induced Apoptosis and Activates PI3K/Akt/mTOR Pathway in H9c2 Cardiomyocyte Cell Line - Hua Li; Yibin Liu; Sha Tang; Jie Hu; Qiuling Wu; Yang Wei; Ming Niu (Cardiovascular Toxicology, 2021)

Acute associations between air pollution on premature rupture of membranes in Hefei, China - Chao Zhang; Sha Li; Gan-lan Guo; Jing-wen Hao; Peng Cheng; Li-lin Xiong; Shu-ting Chen; Ji-yu Cao; Yu-wen Guo; Jia-hu Hao (Environmental Geochemistry and Health, 2021)

Occurrence of heavy metals, antibiotics, and antibiotic resistance genes in different kinds of land-applied manure in China - Jiajia Xue; Jianqiang Wu; Yaru Hu; Chenyan Sha; Shijie Yao; Peng Li; Kuangfei Lin; Changzheng Cui (Environmental Science and Pollution Research, 2021)

Serum Iron and Ferritin Levels Are Correlated with Complement C3 - Shuang Wen; Yeqin Sha; Yinling Li; Zhilian Rui; Chenhong Si; Yuning Zhou; Fengfeng Yan; Bicheng Wang; Jingming Hu; Xu Han; Dongyan Shi (Biological Trace Element Research, 2021)

The effect of aging on VEGF/VEGFR2 signal pathway genes expression in rat liver sinusoidal endothelial cell - Wan-Li Wang; Xing-Long Zheng; Qing-Shan Li; Wen-Yan Liu; Liang-Shuo Hu; Huan-Chen Sha; Kun Guo; Yi Lv; Bo Wang (Molecular and Cellular Biochemistry, 2021)

TNF-α suppresses sweat gland differentiation of MSCs by reducing FTO-mediated m6A-demethylation of Nanog mRNA - Yihui Wang; Rui Wang; Bin Yao; Tian Hu; Zhao Li; Yufan Liu; Xiaoli Cui; Liuhanghang Cheng; Wei Song; Sha Huang; Xiaobing Fu (Science China Life Sciences, 2020)

Predicting the higher heating value of syngas pyrolyzed from sewage sludge using an artificial neural network - Hongsen Li; Qi Xu; Keke Xiao; Jiakuan Yang; Sha Liang; Jingping Hu; Huijie Hou; Bingchuan Liu (Environmental Science and Pollution Research, 2020)

Deubiquitylatinase inhibitor b-AP15 induces c-Myc-Noxa-mediated apoptosis in esophageal squamous cell carcinoma - Beibei Sha; Xiaoyu Chen; Han Wu; Miaomiao Li; Jianxiang Shi; Longhao Wang; Xingge Liu; Ping Chen; Tao Hu; Pei Li (Apoptosis, 2019)

Effects of different levels of sweet potato in feeds on body composition and digestive enzymes activities of Apostichopus japonicas Selenka - Bin Zhao; Wei Hu; Chenglin Li; Sha Han; Tao Xu (Journal of Oceanology and Limnology, 2018)

Global environmental costs of China's thirst for milk - Zhaohai Bai; Michael R. F. Lee; Lin Ma; Stewart Ledgard; Oene Oenema; Gerard L. Velthof; Wenqi Ma; Mengchu Guo; Zhanqing Zhao; Sha Wei; Shengli Li; Xia Liu; et al. (Global Change Biology, 2018)
China has an ever‐increasing thirst for milk, with a predicted 3.2‐fold increase in demand by 2050 compared to the production level in 2010. What are the environmental implications of meeting this demand, and what is the preferred pathway? We addressed these questions by using a nexus approach, to examine the interdependencies of increasing milk consumption in China by 2050 and its global impacts, under different scenarios of domestic milk production and importation. Meeting China's milk demand in a business as usual scenario will increase global dairy‐related (China and the leading milk exporting regions) greenhouse gas ( GHG ) emissions by 35% (from 565 to 764 Tg CO 2eq ) and land use for dairy feed production by 32% (from 84 to 111 million ha) compared to 2010, while reactive nitrogen losses from the dairy sector will increase by 48% (from 3.6 to 5.4 Tg nitrogen). Producing all additional milk in China with current technology will greatly increase animal feed import; from 1.9 to 8.5 Tg for concentrates and from 1.0 to 6.2 Tg for forage (alfalfa). In addition, it will increase domestic dairy related GHG emissions by 2.2 times compared to 2010 levels. Importing the extra milk will transfer the environmental burden from China to milk exporting countries; current dairy exporting countries may be unable to produce all additional milk due to physical limitations or environmental preferences/legislation. For example, the farmland area for cattle‐feed production in New Zealand would have to increase by more than 57% (1.3 million ha) and that in Europe by more than 39% (15 million ha), while GHG emissions and nitrogen losses would increase roughly proportionally with the increase of farmland in both regions. We propose that a more sustainable dairy future will rely on high milk demanding regions (such as China) improving their domestic milk and feed production efficiencies up to the level of leading milk producing countries. This will decrease the global dairy related GHG emissions and land use by 12% (90 Tg CO 2eq reduction) and 30% (34 million ha land reduction) compared to the business as usual scenario, respectively. However, this still represents an increase in total GHG emissions of 19% whereas land use will decrease by 8% when compared with 2010 levels, respectively.

Effects of dietary fresh fermented soybean meal on growth performance, ammonia and particulate matter emissions, and nitrogen excretion in nursery piglets - Sai-sai Cheng; Yuan Li; Shi-jie Geng; Luan-sha Hu; Xiong-feng Fu; Xin-yan Han (Journal of Zhejiang University-SCIENCE B, 2017)

Brain abnormalities in fucosidosis: transplantation or supportive therapy? - Minyan Jiang; Sha Liu; Hua Jiang; Yunting Lin; Yongxian Shao; Hao Hu; Xiaoyuan Zhao; Hongsheng Liu; Yonglan Huang; Li Liu (Metabolic Brain Disease, 2017)

Fatality risks for nosocomial outbreaks of Middle East respiratory syndrome coronavirus in the Middle East and South Korea - Jianping Sha; Yuan Li; Xiaowen Chen; Yan Hu; Yajin Ren; Xingyi Geng; Zhiruo Zhang; Shelan Liu (Archives of Virology, 2017)

Effect of tidal stress on fault nucleation and failure of the 2007 M s6.4 Ning’er earthquake - ChaoDi Xie; XingLin Lei; XiaoPing Wu; Hong Fu; ZiYao Xiong; XiongLin Hu; Sha Li (Science China Earth Sciences, 2016)

The miR-573/apoM/Bcl2A1-dependent signal transduction pathway is essential for hepatocyte apoptosis and hepatocarcinogenesis - Yan-Wei Hu; Zhi-Ping Chen; Xiu-Mei Hu; Jia-Yi Zhao; Jin-Lan Huang; Xin Ma; Shu-Fen Li; Yu-Rong Qiu; Xiao-Juan Wu; Yan-Hua Sha; Ji-Juan Gao; Yan-Chao Wang; et al. (Apoptosis, 2015)

Development of In Vitro Macrophage System to Evaluate Phagocytosis and Intracellular Fate of Penicillium marneffei Conidia - Sha Lu; Yongxuan Hu; Changming Lu; Junmin Zhang; Xiqing Li; Liyan Xi (Mycopathologia, 2013)

Microparameter Prediction for a Triaxial Compression PFC3D Model of Rock Using Full Factorial Designs and Artificial Neural Networks - Miao-jun Sun; Hui-ming Tang; Xin-li Hu; Yun-feng Ge; Sha Lu (Geotechnical and Geological Engineering, 2013)

Chromoblastomycosis in Mainland China: A Systematic Review on Clinical Characteristics - Sha Lu; Changming Lu; Junmin Zhang; Yongxuan Hu; Xiqing Li; Liyan Xi (Mycopathologia, 2013)

Melanin in a Meristematic Mutant of Fonsecaea monophora Inhibits the Production of Nitric Oxide and Th1 Cytokines of Murine Macrophages - Junmin Zhang; Li Wang; Liyan Xi; Huaiqiu Huang; Yongxuan Hu; Xiqing Li; Xiao Huang; Sha Lu; Jiufeng Sun (Mycopathologia, 2013)

Genome-wide association study identified novel genetic variant on SLC45A3 gene associated with serum levels prostate-specific antigen (PSA) in a Chinese population - Jielin Sun; Sha Tao; Yong Gao; Tao Peng; Aihua Tan; Haiying Zhang; Xiaobo Yang; Xue Qin; Yanling Hu; Junjie Feng; Seong-Tae Kim; Xiaoling Lin; et al. (Human Genetics, 2013)

Blockade of HERG K+ channel by isoquinoline alkaloid neferine in the stable transfected HEK293 cells - Dong-fang Gu; Xue-lian Li; Zhi-ping Qi; Sha-shan Shi; Mei-qin Hu; Dong-min Liu; Cheng-bai She; Yan-jie Lv; Bao-xin Li; Bao-feng Yang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2009)

Association of the DRD2 and DRD3 polymorphisms with response to pramipexole in Parkinson’s disease patients - Ying-Zi Liu; Bei-Sha Tang; Xin-Xiang Yan; Jie Liu; Dong-Sheng Ouyang; Li-Nuo Nie; Lan Fan; Zhi Li; Wei Ji; Dong-Li Hu; Dan Wang; Hong-Hao Zhou (European Journal of Clinical Pharmacology, 2009)

Immunogenicity and relative attenuation of different vaccinia-rabies virus recombinants - J. -H. Zhu; J. Wang; B. Cai; W. Zhao; Y. Zhu; R. Chao; L. Chen; H. Xue; B. L. Ying; C. P. Li; Q. L. Hu; J. Sha; et al. (Archives of Virology, 1996)